A systematic review on factors influencing the development of children’s creativity - Smare, Zaina; Elfatihi, Mohamed (Journal of childhood, education & society (Online), 2024)
No one can deny that creativity is essential for survival and a key skill for prosperity in the 21st century. In an era where the skill of creativity is the pathway to development, it is crucial that we nurture children's creativity to better prepare them for academic, professional, and personal success. Systematic reviews on factors that could support or impede children’s creativity is scarce. The present review was conducted to fill this gap. Major electronic databases were searched and studies meeting predetermined selection criteria were analyzed. The search yielded 55 studies published between 2010 to 2022 in English. We classified influencing factors into four types: individual, family, educational, and socio-cultural factors. We concluded by discussing recommendations for parents, educational stakeholders and researchers.